1990
DOI: 10.1210/endo-126-2-1283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ACTH on VIP and Galanin Release from the Pituitary*

Abstract: The effect of adrenocorticotropin (ACTH) on the release of four regulatory peptides from the anterior pituitary of male rats has been studied using an in vitro perfusion system. Quartered anterior pituitaries from male adult Wistar rats were perfused with buffer containing different concentrations of ACTH and, subsequently, 56 mM KCl. Fractions of 1.5 ml were collected at 3 min intervals and analyzed for vasoactive intestinal peptide (VIP), galanin, 7B2, and substance P, using specific radioimmunoassays. Conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Studies on female rats with an altered galanin gene have confirmed that proliferation of lactotrophs under a high dose of oestrogen can be completely abolished (Wynick et al, 1998b), but galanin has also been associated with many other pituitary functions, such as the release of GH or LH, FSH and ACTH in humans. For further reading, we recommend the following references (Vrontakis et al, 1989(Vrontakis et al, , 1996Gabriel et al, 1989Gabriel et al, , 1990Calvo et al, 1990;Hooi et al, 1990aHooi et al, , 1997O'Halloran et al, 1991;Hyde and Howard, 1992;Niimi et al, 1993;Moore et al, 1994;Giustina et al, 1994;Hyde et al, 1996Hyde et al, , 1998Sauer-Ramirez et al, 1996;Hammond et al, 1997;Ceresini et al, 1997;Cai et al, 1998;Todd et al, 1998;Baranowska et al, 1999;Ren et al, 1999;Shen et al, 1999;Zdrojewicz and Sowinska, 2000;Elsaesser, 2001). This is in agreement with the presence of galanin in all pituitary cells during development; they all express galanin which, in the adult, may potentially activate specific functions in specific endocrine cells of the pituitary.…”
Section: Discussionsupporting
confidence: 65%
“…Studies on female rats with an altered galanin gene have confirmed that proliferation of lactotrophs under a high dose of oestrogen can be completely abolished (Wynick et al, 1998b), but galanin has also been associated with many other pituitary functions, such as the release of GH or LH, FSH and ACTH in humans. For further reading, we recommend the following references (Vrontakis et al, 1989(Vrontakis et al, , 1996Gabriel et al, 1989Gabriel et al, , 1990Calvo et al, 1990;Hooi et al, 1990aHooi et al, , 1997O'Halloran et al, 1991;Hyde and Howard, 1992;Niimi et al, 1993;Moore et al, 1994;Giustina et al, 1994;Hyde et al, 1996Hyde et al, , 1998Sauer-Ramirez et al, 1996;Hammond et al, 1997;Ceresini et al, 1997;Cai et al, 1998;Todd et al, 1998;Baranowska et al, 1999;Ren et al, 1999;Shen et al, 1999;Zdrojewicz and Sowinska, 2000;Elsaesser, 2001). This is in agreement with the presence of galanin in all pituitary cells during development; they all express galanin which, in the adult, may potentially activate specific functions in specific endocrine cells of the pituitary.…”
Section: Discussionsupporting
confidence: 65%
“…However, it has previously been reported that the secretion of both GAL and ACTH from human ACTH‐secreting tumours in culture is stimulated dose‐dependently by corticotropin releasing hormone (Invitti et al. , 1999) and ACTH has been shown to stimulate GAL release from rat pituitary in vitro (Calvo et al. , 1990).…”
Section: Discussionmentioning
confidence: 99%
“…After I h the medium was replaced by one containing TRH at concentrations of 1 • 10 -5 M, i X 10 -7 M or 1 x 10 -9 M. (Ottlecz et al, 1988;Koshiyama et al, 1987Koshiyama et al, , 1990 Cells were cultured overnight then incubated on the membrane in the presence of I x 10 -6 M galanin. (Calvo et al, 1990) Cells from male rats were cultured overnight then incubated on the membrane in graded concentrations (2 x 10 -sM, 2 x 10 -TM, 4 x 10 -7M, lX 10 -~ of ACTH.…”
Section: Methodsmentioning
confidence: 99%